Evaluation of ginger extract’s yield, using cold extraction method and its antimicrobial activity against pathogens - Gautam, Bikram; Nepal, Richa; Bhandari, Rupa; Gyawali, Shishir (Asian Journal of Medical and Biological Research, 2019)
Ginger is commonly used herb across the world either in a meal or in herbal products. The chemical constituents of ginger possess antioxidants, can modulate apoptosis, inhibit vascular endothelial growth factor and inhibit inflammatory reactions. The main aim of this study is to assess the antimicrobial activity of the ginger extracts. For this purpose, ginger rhizome (R), packaged ginger powder (P) and ginger leaves (L) were collected from Urlabari, Morang and Kathmandu, Nepal. The plant materials were first minced (except P) and then extracted using cold extraction technique. For assessing the antimicrobial activity of the extracts against the American Type Culture Collection (ATCC) strains, cup well method was preferred. The percentage yield of extracts R, P, L and ginger rhizome’s juice (J) was 10.79 ± 0.03 %, 9.76 ± 0.16 %, 8.17 ± 0.07 % and 16.8 ± 1.98 % respectively. The extract R were found to susceptible against the pathogens Streptococcus pneumoniae, Klebsiella pneumoniae, Escherichia coli, Staphylococcus aureus and methicillin resistant Staphylococcus aureus (MRSA). The extract P were found to susceptible against the pathogens E. coli, S. aureus and MRSA. The methanol extract of L was found to be susceptible to S. aureus, K. pneumoniae and MRSA. All the extracts (R, P, L) were reistant against Pseudomonas aeruginosa. All 6 bacterial isolates were resistant against the extract J. The extract shows antimicrobial property only when the extract is concentrated. The ginger leaves also have antimicrobial property. Asian J. Med. Biol. Res. March 2019, 5(1): 8-13